Indicators of Populus nigra L. leaf blade asymmetry and their bioindicative informativeness (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
We have evaluated the dynamics and bioindicative informative of Populus nigra L. leaf blade asymmetry indicators: the degree of pseudo-symmetry form of the leaf blade in general, the asymmetry coefficient of shape of the top, and the asymmetry coefficient of shape of the base. Value of the pseudo-symmetry forms index varies from 0,5485 to 0,9796. The value of the asymmetry coefficient of shape of the top for all samples varies from 0,000 to 0,253, and of the asymmetry coefficient of shape of the base – from от 0,000 to 0,152. The asymmetry coefficient of shape of the base is the best indicator of the environment state of the three analyzed parameters of P. nigra leaf blade asymmetry. This index divides best samples of the leaf blades from less transformed ecosystems and ecosystems with significant anthropogenic pressure.
Keywords: leaf blade, assimetry, bioindication, discriminant analysis, Рopulus nigra L.